Dakwah Pada Masyarakat Miskin Kultural - Naharin, Sri (Mafa Press, 2023)
People who live in a poor culture which then leads them to become culturally poor is a tough challenge for da'wah. So to answer these challenges, it is necessary to elaborate the meaning of da'wah conceptually - philosophically and practically - implementatively to determine methods that are considered more relevant. And then it will be arranged to offer the right da'wah strategy within the framework of social engineering for the actions of social change - the culture of the cultural poor. Where the da'wah strategy with a philosophical-anthropological approach is applied applicatively - strategically to the five elements in da'wah, namely the subject (da'i), material (maddah), method (thariqah), media (washilah), and object (mad'u). This research is a type of library research and is qualitative-descriptive, where written data in the form of books, journals, documents, records of events as primary and secondary data sources. The analysis of this research uses the culture of poverty theory to analyze the cultural problems of the cultural poor as a recommendation and basis for preparing da'wah strategies in the cultural poor.